EXTH-102. PLASMA AND CEREBROSPINAL FLUID (CSF) PHARMACOKINETICS (PK) OF MIRDAMETINIB IN A NON-HUMAN PRIMATE (NHP) MODEL. (14th November 2022) - McCully, Cynthia Lester; Shearer, Todd; Gross, Andrea; Langseth, Abraham; Peer, Cody; Killoran, Kristin; Garcia, Rafael Cruz; Figg, William; Widemann, Brigitte
Abstract: Mirdametinib is a MEK inhibitor with reported CSF penetration in pre-clinical models. Murine studies reported ERK phosphorylation inhibition in brain tissue at 1.15 nM (0.73 ng/mL) and tumor cell lines at 0.33–0.59 nM (0.16-0.28 ng/mL). A phase II clinical trial evaluating mirdametinib for neurofibromatosis type 1-related plexiform neurofibromas reported a 42% partial response rate and a mean plasma exposure (AUC0-12h ) of 443 h*ng/mL. This study determined the plasma and CSF pharmacokinetic (PK) profile of mirdametinib in a non-human primate (NHP) model where CSF penetration serves as a proxy for CNS penetration. METHODS: Four NHP received mirdametinib PO q.d, 0.50 mg/kg, in serial studies as a single dose (Single-Dose), three doses (Multiple-Dose), or IV, 0.20 mg/kg, followed by paired plasma and CSF sample collections through 96 hours. Mirdametinib was quantified by LC-MS/MS. PK parameters were calculated via noncompartmental methods. Plasma protein binding was determined by rapid equilibrium dialysis. RESULTS: Mean □ standard deviation values reported. Three subjects were evaluable for both plasma (total and unbound) and CSF drug concentrations. Plasma – AUClast : Single-Dose 500.3 □ 253.4 and IV 552.3 □ 43 h*ng/mL; AUCtau : Multiple-Dose 456.3 □ 120.6 h*ng/mL. CSF Cmax (ng/mL): Single-Dose 0.43 □ 0.18, IV 2.0 □ 1.8, Multiple-Dose 0.56 □ 0.18. CSF Penetration (%): Single-Dose 1.3 □ 0.45, IV-1.6 □ 0.95 (AUCcsf-last :AUCplasma-last ); Multiple-Dose 1.3 □ 0.56 (AUCcsf-tau :AUCplasma-tau ). CSF/unbound plasma ratios ranged from 2.5-3.0 Plasma free fraction (%): 0.52 □ 0.1. CONCLUSION: Notable mirdametinib CSF penetration was demonstrated in this NHP model. A higher CSF to unbound plasma ratio suggests that the efflux of mirdametinib from the CSF was delayed. The NHP CSF Cmax approached the ERK phosphorylation inhibition concentrations previously reported. The ability of this NHP model to predict human PK parameters was demonstrated via the comparable NHP to patient plasma exposure reported in the Phase II clinical trial.